High-resolution LIF-Imaging of the oil film thickness in the piston-ring / cylinder-liner contact in an optical tribometer. (July 2020) - Cheong, Jiyeon; Wigger, Stefan; Füßer, Hans-Jürgen; Kaiser, Sebastian A.
Abstract: An optical tribometer is developed as a model experiment for the piston-ring/cylinder-liner assembly in an internal combustion engine. The tribometer replaces the reciprocating movement of the piston rings by the steady rotation of the cylinder liner against whose inside running surface a stationary piston-ring segment from sapphire is pressed. Through this transparent ring segment, the oil-film thickness was imaged by laser-induced fluorescence of a dye added to the oil. The images clearly show various oil-filled structures of the liner surface. After an in-situ calibration and stray-light correction, the minimum film thickness was quantitatively evaluated and compared to the corresponding friction coefficient. Compared to honed cast iron, pores in a spray-coated liner retain more oil and reduce friction at higher loads. Highlights: New optical tribometer models sliding contact between engine cylinder-liner and piston ring. Optical access to contact zone through a quartz piston-ring segment and fluorescence imaging of dyed oil. Production liner surface from honed cast iron or thermal spray coating. Oil-film thickness quantified via in-situ calibration and stray-light correction. At higher loads and lower speeds, pores from spray coating are tribologically advantageous.